Scintiscan Characteristics of Normal Thyroid Gland in a Region of Known Iodine Intake - Krishnamurthy, G. T.; Snoop, Lucille E. (Nuklearmedizin - NuclearMedicine, 1976)
Morphological features of a normal thyroid gland in a geographical region where the daily iodine intake is about 1 mg are established. The mean weight of the thyroid gland is 31.3 gm with a range from 19 to 43 gm. Oblique length of the right lobe is 5.0 cm and that of the left lobe 4.8 cm. The surface area of the right and left lobes is 9.7 and 9.1 cm2, respectively. The weight of the thyroid gland calculated on the basis of the scan obtained with 99mTcO4 is quite variable and shows poor correlation (γ = 0.40) with the weight obtained on the basis of I-131 scan. It is suggested that the criteria of normalcy be established regionally based on iodine intake, and that an isotope of iodine be used in calculating the weight of thyroid gland for dosimetry purposes.